Early Visual Attention in Preterm and Fullterm Infants in Relation to Cognitive and Motor Outcomes at School Age: An Exploratory Study - Hitzert, Marrit M.; Van Braeckel, Koenraad N. J. A.; Bos, Arend F.; Hunnius, Sabine; Geuze, Reint H. (Frontiers in Pediatrics, 2014)
Objective: Preterm infants are exposed to the visual environment earlier than fullterm infants, but whether early exposure affects later development is unclear. Our aim was to investigate whether the development of visual disengagement capacity during the first six months after term was associated with cognitive and motor outcomes at school age, and whether associations differed between fullterms and low-risk preterms. Method: Seventeen fullterms and ten low-risk preterms were tested in a gaze shifting task every four weeks until six months postterm. The longitudinal data were converted into single continuous variables by fitting the data with an S-shaped curve (frequencies of looks) or an inverse model (latencies of looks). Neuropsychological test results at school age were converted into composite z scores. We then performed linear regression analyses for each functional domain at school age with the variables measuring infant visual attention as separate predictors and adjusting for maternal level of education and group (fullterms versus preterm). We included an interaction term, visual attention*group, to determine whether predictive relations differed between fullterms and preterms. Results: A slower development of disengagement predicted poorer performance on attention, motor skills, and handwriting, irrespective of fullterm or preterm birth. Predictive relationships differed marginally between fullterms and preterms for inhibitory attentional control (P =.054) and comprehensive reading (P =.064). Conclusions: This exploratory study yielded no indications of a clear advantage or disadvantage of the extra visual exposure in healthy preterm infants. We tentatively conclude that additional visual exposure does not interfere with the ongoing development of neuronal networks during this vulnerable period of brain development.